Deprescribing practice in a resource‐limited setting: Healthcare providers' insights. Issue 9 (24th May 2021) - Tegegn, Henok Getachew; Gebresillassseie, Begashaw Melaku; Erku, Daniel Asfaw; Elias, Asrat; Yabeyu, Abdella Birhan; Ayele, Asnakew Achaw
Abstract: Aims: Inappropriate polypharmacy poses risks of adverse drug events, high healthcare costs and mortality. Deprescribing could minimise inappropriate polypharmacy and the consequences thereof. The aim of this study was to evaluate healthcare providers' (HCPs') attitudes toward and experiences with deprescribing practice in Ethiopia. Methods: We conducted an institution‐based cross‐sectional survey among HCPs at the University of Gondar Comprehensive Specialized Hospital, Ethiopia. We used a validated questionnaire developed by Linsky et al. The tool included questions that explore medication characteristics, current patient clinical factors, predictions of future health states, patients' resources to manage their own health and education and experience. One‐way ANOVA was used to test the association between sociodemographic variables and their perception of deprescribing decisions. Results: Of 85 HCPs approached, about 82 HCPs completed the survey, giving a response rate of 96.5%. Most of the participants (n = 73, 89%) have scored less than 1.5 points showing they are reluctant to proactively deprescribe. Physicians seem to be affected by the significant physical health conditions (mean = 1.68) and clinical endpoint like blood pressure (mean = 1.5) to make deprescribing decisions. According to the post hoc analysis of one‐way ANOVA, clinical pharmacists seemed to have a better attitude toward deprescribing decisions compared with physicians ( P = .025). Conclusion: HCPs' decision to discontinue a medication could be multifactorial. Physicians could be influenced by physical health condition and clinical endpoints for deprescribing decision. Future studies should emphasise on barriers and facilitators to deprescribing practice specific to the context in Ethiopia.